Chemical profiling and antibacterial activity of javanese turmeric (Curcuma xanthorriza) essential oil on selected sound pathogen - , Suryati, Dachriyanus; Jaswir, Irwandi; Yusof, Faridah (Atlantis Press, 2021)
Essential oil is a volatile liquid with a pungent taste and aroma. The essential oil has been used since many years ago for many purpose including as antimicrobial agent. Javanese turmeric reported containing essential oil. Therefore, the purpose of this study was to identify chemical profiling of essential oil of Javanese turmeric (Curcuma xanthorriza) rhizome which collected from Padang, West Sumatera as well as to evaluate antibacterial activity toward selected wound infected bacteria. The hydrodistillation technique was used for extracting the essential oil and the chemical profiling was identified by using gas chromatography-mass spectrometry (GC-MS). The percentage of essential oil obtained was 0.557 %. The result revealed the essential oil of rhizome contained α-Curcumene, β-Curcumene, Di-epi-..-cedrene-(I), (-)-Xanthorrhizol, and S-(-)-Camphor as major constituents. Antibacterial activity was performed by broth microdilution technique The essential oil was active against test bacteria with the Minimum Inhibition Concentration (MIC) value was 5 mg/ml, 6.25 mg/ml and 10 mg/ml for Staphylococcus epidermidis, Staphylococcus aureus and Enterococcus faecalis respectively